ASSOCIATION BETWEEN SOCIO-DEMOGRAPHIC FEATURES AND INTENTION OF FARMERS TO USE ICTS FOR AGRICULTURAL RISK MANAGEMENT IN MALAYSIA - M. Ali; N. Man; F. M. Muharam (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2019)
Farmers intention’to use ICTs for agricultural risk management is increasing not only in Malaysia but also in Asia and other parts of the world. Although much research has been conducted to examine association between socio-demographic characteristics of farmers and behavioral intention to use ICT in various contexts but less attention has been paid towards farmers intention’ to use ICTs in the perspective of agricultural risk management. Therefore, present study was conducted in three zones of Malaysia where natural disasters like floods and landsliding had caused serious concern. The data were collected from 360 farmers through structured questionnaire by using multistage cluster sampling technique. The collected data were analyzed by uing SPSS as data analysis tool. The results reveal that there is positive and significant association between education (P< 0.00), size of dependents (P< 0.00), land ownership (P< 0.02) and annual income (P< 0.00) with intention of farmers to use ICTs for the management of agricultural risk (s). Conversely, there is no significant association between age, experience and farm size with intention of farmers to use ICTs for agricultural risk management. In conclusion, education, dependents size, land ownership and annual income were important factors which affected utilization of ICTs for agricultural risk management in Malaysia. The study recommends that more research should be conducted in other parts of the country. Moreover, all stakeholders and particularly agricultural extension officers should actively work to scale up ICT usage in the agricultural sector.